(untitled) (SCIENCE TIME JOURNAL, 2026)
Coverage of President Trump’s visit to Beijing on 13–1614-15 May 2026 by three American news organizations, The New York Times, CNN, and Fox News, is analyzed by a combined pragmatic and multimodal analysis. Each outlet builds its perspective of the meeting between the U.S. and Chinese leaders through distinct verbal architecture, attribution patterns, evaluative resources, and image-text relations. The same event becomes three different discursive objects, and newspapers within the broadly liberal segment of American journalism diverge from one another nearly as much as they diverge from conservative outlets. The combined procedure of pragmatic and multimodal analyses are needed to capture differences that neither tool alone would cover.